Cataract Remains an Important Cause of Blindness in Campinas, Brazil - Leite Arieta, Carlos Eduardo; de Oliveira, Denise Fornazari; de Carvalho Lupinacci, Alvaro Pedroso; Novaes, Priscila; Paccola, Marcelo; Jose, Newton Kara [UNESP]; Limburg, Hans (Taylor & Francis Inc, 2009)
Objective: To estimate the prevalence of blindness in the elderly population of Campinas, Brazil, and to describe the coverage and quality of cataract surgery services in the area. Methods: A brief assessment of cataract surgery services (using the RACSS (Rapid Assessment of Cataract Surgical Services Method) was conducted using random cluster sampling, with a sample composed of 60 clusters of 40 people aged 50 years or older. Visual acuity (VA) was measured and the lens status observed by direct visual ophthalmoscopy. From the selected sample of 2,400 subjects, 92.67% were examined. Results: Blindness (VA 3/60 with available correction) was found in 1.98 % (2.03 % among male subjects, and 1.94 % among female subjects). The prevalence of blindness varied with age, from 0.2%, in the group from 50 to 54 years, to 7.2% in those above 80. Cataract was the main cause of blindness (40.2%) followed by suspected posterior segment disorders (18.2%), diabetic retinopathy (15.9%), and glaucoma (11.4%). The cataract surgical coverage was of 93% (VA 3/60) and 82.18% when the criterion was VA 6/60 in the best eye. The main reasons the subjects did not receive surgical treatment were: fear of undergoing surgery, 11.1%; lack of awareness about the condition, 16.7%; waiting for maturity, 16.7%; and contraindication to surgery, 44.4%. Conclusion: Cataract is the major cause of blindness in Campinas. Education on eye diseases, their prevention and treatment must become part of the city's public healthcare policies.
Keywords: Blindness; cataract prevalence; causes; pseudophakia; Campinas; Brazil